The Impact of CoRong Ajar on Teachers’ Understanding to Enhance Self-Control in Children Exposed to Violence - Lalita, Maya Nirmala Tyas; Salim, Rose Mini Agoes (FKIP Universitas Lampung, 2025)
The Impact of CoRong Ajar on Teachers’ Understanding to Enhance Self-Control in Children Exposed to Violence. Objectives: The purpose of this study was to examine the effectiveness of the CoRong Ajar program (Model, Encourage, and Teach) in enhancing teachers' understanding of how to improve self-control in children aged 4 to 8 who have been exposed to violence. Methods: A quasi-experimental design using a one-group pretest and posttest method was applied. A total of 11 teachers participated in the study. They all worked directly with children who had experienced different forms of violence. Participants were chosen based on their roles in both education and psychosocial support. The objective test was used to evaluate participants' understanding of the program. This instrument was developed to align with the content and objectives of the CoRong Ajar program. Data were analyzed using the Friedman Test to examine overall changes and the Wilcoxon Signed-Rank Test to compare differences between specific time points. Findings: The results showed a significant improvement in participants' understanding. The mean scores increased from pretest (8.78) to posttest (10.9) and further to the follow-up test (13.1). The Friedman Test also revealed a statistically significant difference across the three time points (p < 0.05). It indicated an effect of the overall intervention. Additionally, the Wilcoxon Signed-Rank Test confirmed significant pairwise differences between the pretest and posttest, the posttest and follow-up test, and the pretest and follow-up test. Conclusion: CoRong Ajar program revealed effectiveness in enhancing teachers' understanding of how to teach self-control in children aged 4 to 8 who have been exposed to violence. The findings of this study provide a valuable reference for handling low self-control in children exposed to violence that is applicable within school environments. Keywords: children abused, CoRong Ajar, early childhood, moral development, self-control.